Las manualidades en el desarrollo de la creatividad en niños y niñas de 4 a 5 años de edad de la unidad educativa “Verbo Divino”, cantón Guaranda, provincia Bolívar, periodo 2024 - Lizano Toapanta, Silvia Elizabeth (2025)
This research focuses on analyzing the role of crafts in the development of creativity in boys and girls aged 4 to 5, from Initial 2 parallel "B" of the "Verbo Divino" Educational Unit, in the 2024 academic period. Through the analysis through observation, it was found that in Initial 2 parallel "B" of the "Verbo Divino" Educational Unit, it was observed that they have the necessary material to make crafts, but they will not implement it because there is a considerable number of children and a single teacher cannot attend to everyone adequately. Within our theoretical framework, solid information is shown that allows a clear understanding of the two variables, the first deals with crafts, a compilation of information is shown that is related to the definition of crafts, importance, types, benefits, effects, among others. In addition, in the second variable we have important topics related to creativity, definition, what it is for, why creativity should be developed, benefits, importance; The same ones that were obtained from reliable sites and sources so that they can later be analyzed, argued and cited correctly. The methodology details the different approaches, methods, types of study design and the techniques and instruments for data collection. The observation form that was executed to the children from 4 to 5 years old, from Initial 2 parallel "B" of the Educational Unit "Verbo Divino", where it allowed us to observe the deficiencies that each one of the infants had, likewise the interview that was directed to the teacher who teaches classes in Initial II was applied, the effects of participation in crafts as a development of the creativity of the children were observed. The same ones that showed interest in the practices of crafts, showing joy at the time of social and individual practice.